2013
DOI: 10.1037/a0031249
|View full text |Cite
|
Sign up to set email alerts
|

Links between parents' epistemological stance and children's evidence talk.

Abstract: Recent experimental research highlights young children's selectivity in learning from others. Little is known, however, about the patterns of information that children actually encounter in conversations with adults. This study investigated variation in parents' tendency to focus on testable evidence as a way to answer science-related questions (e.g., causes of climate change, extinction of species) and asked whether this is related to children's own use of evidence in conversation. Parents read a science-them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 35 publications
2
38
0
1
Order By: Relevance
“…Across cultures, caregivers differ in whether and how they draw children's attention to relations and objects (Fernald & Morikawa, 1993;Ogura, Dale, Yamashita, & Murase, 2006;Senzaki, Masuda, Takada, & Okada, 2016), and corresponding cultural differences in disposition toward relations and objects emerge early (Carstensen et al, 2019;Imada, Carlson, & Itakura, 2013;Kuwabara & Smith, 2012;Senzaki et al, 2016;Waxman et al, 2016). Thus, caregivers may impart habitual modes of attending to certain types of information through interactions with their children (e.g., Luce, Callanan, & Smilovic, 2013;Valle, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Across cultures, caregivers differ in whether and how they draw children's attention to relations and objects (Fernald & Morikawa, 1993;Ogura, Dale, Yamashita, & Murase, 2006;Senzaki, Masuda, Takada, & Okada, 2016), and corresponding cultural differences in disposition toward relations and objects emerge early (Carstensen et al, 2019;Imada, Carlson, & Itakura, 2013;Kuwabara & Smith, 2012;Senzaki et al, 2016;Waxman et al, 2016). Thus, caregivers may impart habitual modes of attending to certain types of information through interactions with their children (e.g., Luce, Callanan, & Smilovic, 2013;Valle, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Explicit talk about evidence is also related to science thinking, and previous research found that parents vary in their tendency to talk about evidence when explaining their reasoning (Luce, Callanan, & Smilovic, ; Valle, ). However, little research has explored whether parents' evidence talk relates to children's engagement or learning.…”
Section: Integrating Developmental Science With Practitioner Expertismentioning
confidence: 99%
“…There is also substantial cultural variation in family explanatory talk. Differences in types of causal talk have been uncovered when comparing parents with varied schooling background, income levels, or attitudes about the nature of knowledge (Kurkul & Corriveau, ; Luce, Callanan, & Smilovic, ; Valle, ). For example, Valle () found that highly educated U.S. parents from engineering and science backgrounds focused more on scientific evidence about conflicting claims on topics such as climate change than did parents from other educational backgrounds.…”
Section: Explanatory Conversation and Causal Thinkingmentioning
confidence: 99%